Bactericidal, anti-hemolytic, and anticancerous activities of phytofabricated silver nanoparticles of glycine max seeds - Kumar, K. B. Vijendra; Varadaraju, Kavitha Raj; Shivaramu, Prasanna D.; Kumar, C. M. Hemanth; Prakruthi, H. R.; Shekara, B. M. Chandra; Shreevatsa, Bhargav; Wani, Tanveer A.; Prakasha, K. C.; Kollur, Shiva Prasad; Shivamallu, Chandan (Frontiers in Chemistry, 2024)
Introduction Soybean is a rich source of bioactive components with good nutritional support and is easily available. In the treatment of cancer, green synthesis of silver nanoparticles (AgNPs) from plant-based samples has gained attentions due to its potency and feasibility. In the present study, using soybean extracts (GM), silver nanoparticles are synthesized and analyzed for their anticancer potency. Methods The synthesized GM-AgNPs were characterized via UV–Vis spectroscopy, Fourier transform-infrared (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy-dispersive X-ray (EDX) techniques for further analysis. Antibacterial activity was evaluated using the disc method and anti-hemolysis activity using the in vitro method, followed by anticancer property evaluation by cytotoxicity, cell migration, apoptosis, and cell cycle. Results and discussion Our results showed that the synthesized GM-AgNPs were spiral-shaped with a size range of 5–50 nm. The antibacterial activity against Staphylococcus aureus and Klebsiella pneumoniae showed the maximum zone of inhibition at 250 μg/mL in comparison with gentamicin. On exploring the anti-hemolysis efficiency, at 200 μg/mL, GM-AgNPs showed no hemolysis in comparison to the extract which showed 40% hemolysis. On analysis of GM-AgNPs against the breast cancer cell line, the nanoparticles displayed the IC50 value of 74.04 μg/mL. Furthermore, at the IC50 concentration, cancer cell migration was reduced. The mechanism of action of GM-AgNPs confirmed the initiation of apoptosis and cell cycle arrest in the sub-G0/G1 (growth phase) phase by 48.19%. In gene expression and protein expression analyses, Bax and Bcl-2 were altered to those of normal physiology.